Abolish barriers to diverse enrollment by removing GRE, GMAT requirements. Issue 9 (13th November 2020) - Sutton, Halley
Abstract : Guillermo Prado, Ph.D., is not only the Vice Provost for Faculty Affairs and Dean of the Graduate School at the University of Miami, he is also a double graduate of that institution, having earned his master's degree and doctoral degree from it. It's an experience that helped Prado gain particular insight into the needs of the students and faculty he now serves.